Association between oxidative balance scores and peripheral artery disease in US adults: a cross-sectional study - Zhou, Min; He, Peng-Fei; Zhang, Keren; Deng, Li-Juan; Wang, Ning; Wang, Gang; Yang, Guang-Yao; Ju, Shang (Frontiers in Nutrition, 2025)
BackgroundThe Oxidative Balance Score (OBS) quantifies the overall oxidative stress burden, with higher scores indicating greater antioxidant (relative to prooxidant) activity. This study aimed to examine the association between peripheral arterial disease (PAD) and OBS.Methods and materialsData from the National Health and Nutrition Examination Survey (NHANES, 1999–2004) were analyzed for participants with ankle-brachial index (ABI) measurements. The total Oxidative Balance Score (OBS) comprised a lifestyle OBS (four lifestyle categories) and a dietary OBS (16 dietary factors). Logistic regression analyses evaluated associations between PAD and total OBS, lifestyle OBS, and dietary OBS. Restricted cubic spline (RCS) analyses assessed dose–response relationships between ABI, PAD, and OBS. Mediation analyses investigated the roles of glucolipid metabolism and renal function in the OBS-PAD association. Sensitivity and stratification analyses were conducted to ensure robustness.ResultsThis study included 2,437 eligible adult participants. Logistic regression analysis, adjusted for multiple potential confounders, revealed negative associations between lifestyle OBS (OR = 0.88; 95% CI: 0.79, 1.00), total OBS (OR = 0.97; 95% CI: 0.94, 0.99), and the likelihood of PAD (all p < 0.05). Restricted cubic spline (RCS) analysis demonstrated a linear relationship between total OBS and PAD, with the likelihood of PAD decreasing as total OBS increased p for nonlinearity = 0.736. Dietary OBS, lifestyle OBS, and total OBS all showed positive linear correlations with ABI levels (all p < 0.05). Mediation analysis indicated that fasting plasma glucose (FPG) and creatinine (CREA) mediated 5.9 and 0.8% of the association between total OBS and PAD, respectively (all p < 0.05). Sensitivity analyses confirmed the negative association between total OBS and PAD p < 0.05, supporting the stability of the results. Stratified analyses highlighted the significant influence of Age, particularly in the younger population aged 20–44 years, a group warranting greater attention.ConclusionOur study demonstrated that higher total OBS is associated with a lower likelihood of PAD. Adopting an antioxidant-rich diet alongside a healthy lifestyle may help mitigate PAD risk. Additionally, modulating FPG and CREA levels could offer potential value in addressing the link between low OBS and PAD.